“Antioxidant activity of the essential oil of Clinopodium pulchellum (Kunt) Govaerts “panizara” - Tapia Manrique, Edgar Robert (2017)
Objective: The species Clinopodium pulchellum (Kunt) Govaerts "Panizara" is an aromatic species native to Peru, according to ethnopharmacological data it presents medicinal properties. The objective was to evaluate the activity of radical scavengers and the antioxidant effect of the essential oil of "Panizara" leaves by chemical and biochemical techniques in vitro. Material and Methods: The determination of the antioxidant activity was performed by two methods of discoloration of the radicals DPPH and ABTS, through the spectrophotometric method. Results: The results obtained in the. Mean concentration (IC 50) of 2288,31 μg/mL in Panizara, in Trolox 3,8 μg/mL with the DPPH method. While with the ABTS assay, the IC50 was 30,87 μg/mL in the sample and 17.04 μg/mL in the standard. Conclusion: In conclusion, the results indicate that the essential oil of "Panizara" possesses antioxidant activity. Such activity is due to chemical structure and redox properties, comparable with the international literature.